Age peculiarities of the structure of senior pupils' and students' initiativity - V V Alekseyeva (Peoples' Friendship University of Russia (RUDN University), 2009)
The results of this research of age peculiarities of senior pupils' and students' initiativity based on multimeasureble-functional model of personal structure of their qualities, which gives an opportunity to study, the display of individual peculiarities of initiativity are considered in this article.